A case study on developing students' problem-solving skills through interdisciplinary thematic learning - Zhang, Chuntong; Wang, Pei; Zeng, Xinwu; Wang, Xiaohong (Frontiers in Psychology, 2025)
Interdisciplinary thematic learning, driven by thematic tasks and real-world problems, is an effective vehicle for cultivating students' problem-solving skills and individual development. However, traditional subject-based teaching has long compartmentalized knowledge into discrete academic disciplines, diverging from the nature of real-world problems and their solutions. Although interdisciplinary thematic learning aims at developing students' key abilities for future life, few empirical studies have examined whether interdisciplinary thematic learning has developed Chinese students' problem-solving skills during the compulsory education phase. Moreover, interdisciplinary thematic learning fully develops and makes use of school subject resource, which plays an important role in developing students' problem-solving ability, but ignores the influence of student foundation and social environment and other factors. This study investigates the development of problem-solving skills among 47 middle school students from a compulsory education institution in Sichuan Province mainly adopts interview, observation and case study. The findings indicated that the process of interdisciplinary thematic learning includes three-dimensional support composed of students' foundation, subject resources and social environment, which jointly support the development of interdisciplinary thematic learning, thus realizing the development of students' problem-solving ability. In the future, while continuing the advantages of multi-case studies, we should jointly carry out single-case and quasi-experimental design study to explore the depth of the study. In addition, it is necessary to consider teacher guidance, digital technology and computing thinking skills when choosing research perspectives in the future. From this, more conclusive and comprehensive conclusions and suggestions are put forward.